Earnings Expectation and Graduate Employment:Evidence from Recent Chinese College Graduates - Yang, Po (中国教育学前沿, 2011)
Chinese college graduates have faced increasing labor market competition since the expansion of tertiary education. Given rigid market demand, graduates with realistic earnings expectations may experience a more efficient job search. Using the 2008 MYCOS College Graduate Employment Survey, this study finds that a 1 000 yuan reduction in a graduate鈥檚 reservation wage can significantly increase the probability of finding a job by 66% and increase the likelihood of being employed six months after graduation by 92%. In addition, the gap between the reservation wage and the market wage has a positive impact. By slightly adjusting earnings expectations, college graduates can significantly improve job search efficiency. Market wages should be seen as reference points when adjusting income expectations.
Keywords: reservation wage; graduate employment; earnings expectation